Mengimplementasikan Konsep Sakinah, Mawadah, Warohmah Dalam Berkeluarga Berdasarkan Al-Qur'an - Della Riayatul Qiromah; Laila Nor Vika; Ana Rahmawati (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2024)
Marriage is the longest worship. Islam has regulated all the procedures for marriage according to its sharia, in this Islamic law, marriage is not only about conveying lust between men and women but how to educate children, make the family happy, build a sakinah mawaddah wa rohmah marriage is also regulated in Islam. Marriage is a very heavy agreement before Allah and a commitment that must be carried out. In Islam, all things that must be realized in marriage have been regulated, namely happiness, responsibility, peace, education and mutual affection. In this material, it will be explained how to build a sakinah, mawaddah wa rahmah marriage in the Qur'an which tends more to the letter Al-Baqarah verses 187 and 228, Arrum verse 21, Ali-Imron verse 159, and Al-Furqon verse 74